Influence of surface states and bulk traps on non-equilibrium phenomena at GaAs and GaN surfaces - Miczek, Marcin; Adamowicz, Bogusława; Hashizume, Tamotsu; Hasegawa, Hideki (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The influence of surface state density NSS and bulk non-radiative lifetime t on room temperature photoluminescence quantum efficiency YPL and surface photovoltage (SPV) versus the excitation light intensity F was studied theoretically for GaAs and wurtzite GaN using self-consistent computer simulations. It was demonstrated that SPV(F ) dependences are more sensitive than YPL(F ) to a change in magnitude of NSS, especially for high NSS and at low F, whereas SPV is practically insensitive to t contrary to YPL. The simultaneous measurement of YPL and SPV versus F, combined with rigorous computer analysis, seems to be a very promising method for contactless characterization of the surface and bulk trap parameters.
Optica Applicata, Vol. 35, 2005, nr 3, s. 355-361
Keywords: optyka; gallium arsenide; gallium nitride; surface states; bulk traps; photoluminescence; surface photovoltage